Influence of Shot Peening on AlSi10Mg Parts Fabricated by Additive Manufacturing - Ahmed H. Maamoun; Mohamed A. Elbestawi; Stephen C. Veldhuis (Journal of Manufacturing and Materials Processing, 2018)
The additive manufacturing (AM) of aluminum alloys promises to considerably enhance the performance of lightweight critical parts in various industrial applications. AlSi10Mg is one of the compatible Al alloys used in the selective laser melting of lightweight components. However, the surface defects obtained from the as-built parts affect their mechanical properties, and thus represent an obstacle to using them as final products. This study aims to improve the surface characteristics of the as-built AlSi10Mg parts using shot peening (SP). To achieve this goal, different SP intensities were applied to various surface textures of the as-built samples. The SP results showed a significant improvement in the as-built surface topography and a higher value of effective depth using 22.9 A intensity and Gp165 glass beads. The area near the shot-peened surface showed a significant microstructure refinement to a specific depth due to the dynamic precipitation of nanoscale Si particles. Surface hardening was also detected and high compressive residual stresses were generated due to severe plastic deformation. The surface characteristics obtained after SP could result in a significant improvement in the mechanical properties and fatigue strength, and thus promise performance enhancement for critical parts in various industrial applications.